Involvement of JNK and Caspase Activation in Hoiamide A-Induced Neurotoxicity in Neocortical Neurons - Zhengyu Cao; Xichun Li; Xiaohan Zou; Michael Greenwood; William H. Gerwick; Thomas F. Murray (Marine Drugs, 2015)
The frequent occurrence of Moorea producens (formerly Lyngbya majuscula) blooms has been associated with adverse effects on human health. Hoiamide A is a structurally unique cyclic depsipeptide isolated from an assemblage of the marine cyanobacteria M. producens and Phormidium gracile. We examined the influence of hoiamide A on neurite outgrowth in neocortical neurons and found that it suppressed neurite outgrowth with an IC50 value of 4.89 nM. Further study demonstrated that hoiamide A stimulated lactic acid dehydrogenase (LDH) efflux, nuclear condensation and caspase-3 activity with EC50 values of 3.66, 2.55 and 4.33 nM, respectively. These data indicated that hoiamide A triggered a unique neuronal death profile that involves both necrotic and apoptotic mechanisms. The similar potencies and similar time-response relationships between LDH efflux and caspase-3 activation/nuclear condensation suggested that both necrosis and apoptosis may derive from interaction with a common molecular target. The broad-spectrum caspase inhibitor, Z-VAD-FMK completely inhibited hoiamide A-induced neurotoxicity. Additionally, hoiamide A stimulated JNK phosphorylation, and a JNK inhibitor attenuated hoiamide A-induced neurotoxicity. Collectively, these data demonstrate that hoiamide A-induced neuronal death requires both JNK and caspase signaling pathways. The potent neurotoxicity and unique neuronal cell death profile of hoiamide A represents a novel neurotoxic chemotype from marine cyanobacteria.